The Influence of Autonomy on Teachers' Performance in The Independent Learning Curriculum - Srinur Hatuti, Evi; Pratami, Dewi Arpi (Indonesian Scientific Publication, 2024)
Implementing an independent learning curriculum, which started in 2022, mitigates learning lag or loss due to the pandemic. Through the independent learning curriculum, it is hoped that teachers can have autonomy in designing and determining learning to improve performance. This study aims to see the effect of autonomy on performance. The research method uses a quantitative method. The population in this study consisted of high school teachers who implemented the independent learning curriculum in Bandung City using a sampling technique, namely proportional random sampling. Data analysis used descriptive and verification methods using simple regression tests. The study showed that the tcount value of autonomy was 6.154 with a significant value of 0.000, which is smaller than 0.05, so autonomy can directly affect the performance of high school teachers. Unlike previous studies that broadly explored curriculum challenges or teacher roles, this study examines the direct relationship between autonomy and performance in the specific framework of Indonesia’s educational reforms. The findings aim to provide practical insights for policymakers and school leaders to optimize teacher autonomy, thereby supporting the successful implementation of the Independent Learning Curriculum.